Rapid reduction in Staphylococcus aureus in atopic dermatitis subjects following dupilumab treatment - Simpson, Eric L.; Schlievert, Patrick M.; Yoshida, Takeshi; Lussier, Stephanie; Boguniewicz, Mark; Hata, Tissa; Fuxench, Zelma; De Benedetto, Anna; Ong, Peck Y.; Ko, Justin; Calatroni, Agustin; Rudman Spergel, Amanda K.; et al. (Journal of allergy and clinical immunology, 2023)
[Display omitted] Atopic dermatitis (AD) is an inflammatory disorder characterized by dominant type 2 inflammation leading to chronic pruritic skin lesions, allergic comorbidities, and Staphylococcus aureus skin colonization and infections. S aureus is thought to play a role in AD severity. This study characterized the changes in the host-microbial interface in subjects with AD following type 2 blockade with dupilumab. Participants (n = 71) with moderate-severe AD were enrolled in a randomized (dupilumab vs placebo; 2:1), double-blind study at Atopic Dermatitis Research Network centers. Bioassays were performed at multiple time points: S aureus and virulence factor quantification, 16s ribosomal RNA microbiome, serum biomarkers, skin transcriptomic analyses, and peripheral blood T-cell phenotyping. At baseline, 100% of participants were S aureus colonized on the skin surface. Dupilumab treatment resulted in significant reductions in S aureus after only 3 days (compared to placebo), which was 11 days before clinical improvement. Participants with the greatest S aureus reductions had the best clinical outcomes, and these reductions correlated with reductions in serum CCL17 and disease severity. Reductions (10-fold) in S aureus cytotoxins (day 7), perturbations in TH17-cell subsets (day 14), and increased expression of genes relevant for IL-17, neutrophil, and complement pathways (day 7) were also observed. Blockade of IL-4 and IL-13 signaling, very rapidly (day 3) reduces S aureus abundance in subjects with AD, and this reduction correlates with reductions in the type 2 biomarker, CCL17, and measures of AD severity (excluding itch). Immunoprofiling and/or transcriptomics suggest a role for TH17 cells, neutrophils, and complement activation as potential mechanisms to explain these findings.